Tumour-derived Interleukin 35 promotes pancreatic ductal adenocarcinoma cell extravasation and metastasis by inducing ICAM1 expression - Chongbiao Huang (Nature Portfolio, 2017)
Interleukin-35 (IL-35) is an immune suppressive cytokine produced by T-cells. Here, the authors show that IL-35 is overexpressed by human pancreatic cancer cells and show, in a mouse model, that IL-35 promotes metastasis in an autocrine/paracrine manner via induction of ICAM-1 expression.